Pola Sebaran Kafe di Kota Banjarmasin: Tinjauan Analisis Teori Lokasi - Sophian, Shesa Maulytha; Muttaqin, Hidayatullah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This research aims to determine the spread pattern of coffee shops in Banjarmasin City and whether it has been appropriated with location theories. Data obtained from field surveys and 72 points of coffee shop locations are found. The data are processed and analyzed using the Geographic Information System (GIS) tool, Google Earth Pro for Windows. The output of the GIS data tool is examined utilizing a description approach to find out how coffee shops' spread pattern is viewed from its accessibility level, the degree of competition, and the coffee shops' closeness to the population. The results show that the spread of coffee shops in Banjarmasin City tends to be distributed at locations that have more accessibility than urban villages with a denser population. In general, the coffee shops' areas are favored to be near them, describing high competition and formed agglomerations.